Long-term follow-up of children conditioned with Treosulfan: German and Austrian experience - Beier, Rita; Schulz, A.; Hönig, M.; Eyrich, M.; Schlegel, P.-G.; Holter, W.; Stachel, K. D.; Ehlert, K.; Greil, Johann; Nürnberger, W.; Wößmann, W.; Bader, P.; et al. (Bone marrow transplantation, 2013)
We report the long-term follow-up of children transplanted with Treosulfan (TREO)-based conditioning in Germany and Austria. Nine centres reported a total of 109 transplantations. Patients were stratified according to the paediatric TRM risk score derived from the paediatric BMT registry (PRST) and compared with the historical transplant population of this registry. Underlying diseases were malignancies, immunodeficiencies, and haematologic and metabolic disorders. TREO total dose ranged from 21-42 g/m2. Additional conditioning drugs included fludarabine, thiotepa, melphalan, CY and/or TBI. EFS at 3 years for non-malignant and malignant diseases was 88% and 49%, respectively. Leukaemia patients in remission had a survival of 51% at 3 years; nonremission patients relapsed and died within 18 months. TRM and OS in the low-risk groups 0 and 1 were similar to PRST controls. TRM in the high-risk groups 2 and 3 was markedly lower (9% vs 28% and 13% vs 53%, respectively) than in the PRST group, but OS was similar. In conclusion, TREO-based conditioning regimens in children resulted in excellent engraftment and long-term survival in nonmalignant disease. In high-risk malignancy, low acute toxicity was followed by low TRM but it did not translate into increased survival.